Democratic security policy: history, budget investment and results period 2002 to 2010 (2014)
This work can provide an understanding of the concept of democratic security as an evolving reference budget nation its funding sources and its impact specifically intended as investment defense sector and particularly the military, all framed in policy development democratic security policy and Consolidation of Democratic security for the period between 2002 and 2010 in order to meet one of the purposes of the state as it is to "ensure peaceful coexistence."